Improvement of Learning Outcomes Theme Healthy Is Important Materials For The Human Blood Circulation System Through Project Based Learning (PJBL) Method In Class Va SDN Rejosari 03 Semarang City In 2020 - Qonitat, Mursyidah (Universitas Sebelas Maret, 2020)
This study aims to improve the learning outcomes of the theme of healthy is important material for human blood circulation through the pjbl method in class VA students at SDN Rejosari 03 Semarang. The approach used in this research is classroom action research. The population in this study were students of class VA SD Negeri Rejosari 03 Semarang, totaling 27 students 11 boys and 16 girls. Data was collected by means of tests and observations. Tests are given to determine student learning outcomes, while observation aims to determine the difficulties experienced by students when solving problems given by the teacher. The conclusion of this study is that the learning outcomes of the healthy theme are important in the material of the human circulatory system through the pjbl method in class VA of SD Negeri Rejosari 03 Semarang, obtained in cycle 1 students who reached the KKM only found 15 from 27 students or 55.5% while cycle 2 students which reached the KKM as many as 25 from 27 students or 92.5%.